ANTIFUNGAL EFFECT OF SPICE EXTRACTS - POSSIBLE SOLUTIONS FOR BIOLOGICAL PRESERVATION OF FOOD - Oana MARE ROŞCA (Stefan cel Mare University of Suceava, 2018)
Aromatic plants used as spices are effective sources for food additives, used both as taste correctors and for the purpose of preserving food. The paper aims at identifying aromatic herbal extracts that summarize several qualities: to help improve the taste and olfactory qualities of food, to stimulate digestive secretions by facilitating digestion and, last but not least, to biologically preserve food, contributing to the reduction in the number and amount of synthetic additives. For this purpose, aqueous extracts of Cinnamomum zeylanicum ritidom, Laurus nobilis leaves and Eugenia caryophyllata floral buds, from commercial sources, were prepared. The extracts were tested on saprophytic fungi cultures, which usually infest food by causing alteration and they were obtained using the SER 148 extractor. The Aspergillus, Mucor and Penicillium cultures were made by selection from environment. The extracts of the three spice species have demonstrated significant fungal activity, inhibiting mold growth. The most powerful effect is recorded by the cloves extract, Eugenia caryophyllata, followed by the cinnamon extract. Having in view the results of these experimental studies we consider that spice extracts can be used in the medium term food storage, as they reduce the amount of synthetic preservatives and replace them by natural products.